2022
DOI: 10.1039/d1ob02223g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a cis-4-aminopiperidine-3-carboxylic acid (cis-APiC) residue on mixed-helical folding of unnatural peptides

Abstract: The α/β-peptide 11/9-helix and the β-peptide 12/10-helix belong to “mixed” helices, in which two types of hydrogen bonds with opposite directionality alternate along the helical axis. cis-2-Aminocyclohaxanecarboxylic acid (cis-ACHC) is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Gellman and colleagues used γ-amino-β-prolines as foldamer building blocks and observed the same propensity to form a 12-helix as its carbocyclic analog without interaction of the ring nitrogen atom with the backbone 52 . The related cis -4-aminopiperidine-3-carboxylic acid ( cis -APiC) also forms a helical 12/10-folding as demonstrated by Choi et al 53 . These examples teach that a single additional heteroatom may not be sufficient for new hydrogen bond networks.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Gellman and colleagues used γ-amino-β-prolines as foldamer building blocks and observed the same propensity to form a 12-helix as its carbocyclic analog without interaction of the ring nitrogen atom with the backbone 52 . The related cis -4-aminopiperidine-3-carboxylic acid ( cis -APiC) also forms a helical 12/10-folding as demonstrated by Choi et al 53 . These examples teach that a single additional heteroatom may not be sufficient for new hydrogen bond networks.…”
Section: Introductionmentioning
confidence: 89%
“…Interestingly, they are characterized by a large share of charged and hydrophilic amino acids capable of forming hydrogen bond networks 56 . Nevertheless, it has been observed that most non-natural foldamer types adopt relatively rigid structures in nonpolar solvents 35 , 43 , 44 , while their tendency for folding in aqueous environments is rather rare 33 , 34 , 50 53 .…”
Section: Introductionmentioning
confidence: 99%